2018
DOI: 10.31248/jasvm2018.101
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity of acetamiprid in male Guinea pig (Cavia porcellus)

Abstract: The neonicotinoid insecticides including acetamiprid are widely used in pest-control programs due to their high efficacy and low cost. This study aimed to investigate the impact of acetamiprid on reproductive parameters as well as its ability to generate oxidative stress in male guinea pig. Twenty-four adult male guinea pigs received oral administration of distilled water (control) and 3 different doses (26.67, 40 and 80 mg/kg body weight) of acetamiprid during 90 days. The effects of treatments were studied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Results revealed that co-administration of C. bauchiense leaves ethanolic extract with heavy metal in rabbits does restore CAT, SOD and peroxidase activities and MDA level at the reference values. Kenfack et al (2018) showed similar results in male guinea pigs receiving 80 mg/kg bw of acetamiprid for 90 days, concerning the control group. This was similar to the report made by (Vemo et al, 2017) in guinea pigs exposed to cypermethrin (137.5 mg/kg bw) only, as compared with those co-treated with ethanolic extract of B. engleriana leaves.…”
Section: Discussionsupporting
confidence: 66%
“…Results revealed that co-administration of C. bauchiense leaves ethanolic extract with heavy metal in rabbits does restore CAT, SOD and peroxidase activities and MDA level at the reference values. Kenfack et al (2018) showed similar results in male guinea pigs receiving 80 mg/kg bw of acetamiprid for 90 days, concerning the control group. This was similar to the report made by (Vemo et al, 2017) in guinea pigs exposed to cypermethrin (137.5 mg/kg bw) only, as compared with those co-treated with ethanolic extract of B. engleriana leaves.…”
Section: Discussionsupporting
confidence: 66%
“…This is in tandem with another study which also observed that rats had lower sperm counts after 45 days of acetamiprid and these rats revealed a significant decrease in sperm motility and increased rates of abnormal morphology (Mosbah et al 2018). Exposure to neonicotinoid insecticides as acetamiprid at 26.67, 40, and 80 mg/kg body weight for 90 days leads to a significant reduction in sperm motility and count of epididymal sperm and a significant increment in the rate of abnormal sperms when compared to the control group (Kenfack et al 2018). However, Quinalphos exposure at 1.0 mg/kg resulted in a significant reduction in motility and increment in sperm head defects and DNA damage (Kumari et al 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Reactive oxygen species (ROS) production in the testis leads to oxidative damage and destroys steriodogenesis and spermatogenesis 28 . Some studies showed acetamiprid induced lipid peroxidation and reduced antioxidant enzymatic activity in the testes 12,18 . In the current study, acetamiprid led to lipid peroxidation, GSH depletion, increase in TOS, and decrease in TAS in testis homogenates in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%